The Role of Religious Psychology in Shaping The Character of a Religious in a Teenager - Akhir Pardamean Harahap; Armita Dwi Lestari; Annisa Oktavera; lvira Alvionita (Universitas Muhammadiyah Enrekang, 2023)
Adolescence is a time when a person will find out his own identity. When adolescents look for their own identity, it is necessary to build a legitimate character so that the teenager is not wrong in forming his identity. Even in adolescence a person will tend to follow along, often indecisive in religion, and others. This research was made because of the many problems of adolescents that often arise due to cultural development, as well as the lack of an education system that pays attention to adolescent psychology and social. This research uses library research methods and all data collected from references to books, journals, or documents that are still relevant to the title of this study. A rema ja who has problems in terms of reluctance to be religious can make several efforts, namely filling free time with positive things, such as attending recitations, learning more deeply about religion or can also join Islamic organizations. To solve adolescent problems is not only done by him but also requires the role of parents in it.